Exploring tick-borne pathogens in community dogs in Nepal - Pandey, Gita Sadaula; Pathak, Chet Raj; Thapa, Sunil; Sadaula, Amir; Manandhar, Prajwol; Abdelbaset, Abdelbaset Eweda; Qiu, Yongjin; Kwak, Mackenzie L.; Hayashi, Naoki; Nonaka, Nariaki; Nakao, Ryo (Parasitology international, 2025)
Tick-borne pathogens (TBPs) in dogs are a major global health concern, with their zoonotic importance often being neglected in developing countries due to a lack of surveillance. This study aimed to highlight the incidence of six important TBPs belonging to the genera Babesia, Theileria, Hepatozoon, Anaplasma, Ehrlichia, and Rickettsia in a total of 230 community dogs from two sites: Lumbini and the Kathmandu Valley, of Nepal. A total of 75 (32.6 %) dogs were found to be infected with at least one TBP, with 11 (4.7 %) being co-infected with more than one TBP. The detection rates of TBPs were 13.9 % (n = 32) for Ehrlichia canis, 9.1 % (n = 21) for Anaplasma platys, 8.6 % (n = 20) for Babesia vogeli, and 6.5 % (n = 15) for Babesia gibsoni. None of the samples were positive for Theileria, Hepatozoon, or Rickettsia. There was a significant association between A. platys and E. canis infections, respectively, with the locations from which the samples were collected. Infections of TBPs in community dogs might be the source of infection for pet dogs or even humans in shared habitats. Further studies are needed to determine the prevalence and diversity of TBPs in dogs in other regions of Nepal. As some of these parasites are zoonotic, concerted efforts are required to raise awareness of, and control efforts for, these tick-borne pathogens. [Display omitted] •Studies on tick-borne pathogens (TBPs) in dogs in Nepal are limited.•Community dogs were molecularly examined for piroplasma and rickettsial infections.•32.6 % (75/230) of the dogs were infected with at least one TBP.•Co-infections with multiple TBPs were found in 4.7 % of the dogs.•Ehrlichia canis, Anaplasma platys, Babesia vogeli and Babesia gibsoni were detected.